1997
DOI: 10.1017/s0260305500014191
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Large-Scale Sea-Ice Motion from SSM/I 85.5 GHz Imagery

Abstract: This paper describes the application of an automated cross-correlation technique to pairs of 85.5 GHz Special Sensor Microwave Imager (SSM/I) images to obtain Ice motion over the entire Arctic Basin for a contiguous two month period between December 1993 and January 1994. Although the surface ice information in the imagery is coarse and noisy, the area cross-correlation method is quite successful in picking up ice-motion information. The accuracy of 85.5 GHz SSM/I derived ice motions is evaluated by comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 7 publications
1
30
0
Order By: Relevance
“…Sea ice motion may also be derived from satellite data by estimating the displacement of sea ice features found in two consecutive images from a variety of satellite instruments (e.g., Agnew et al, 1997;Kwok, 2000). The passive microwave sensors provide the longest period of coverage (1979 to present) but their spatial resolution limits the precision of motion estimates.…”
Section: Data Sources and Time Periods Coveredmentioning
confidence: 99%
“…Sea ice motion may also be derived from satellite data by estimating the displacement of sea ice features found in two consecutive images from a variety of satellite instruments (e.g., Agnew et al, 1997;Kwok, 2000). The passive microwave sensors provide the longest period of coverage (1979 to present) but their spatial resolution limits the precision of motion estimates.…”
Section: Data Sources and Time Periods Coveredmentioning
confidence: 99%
“…Since the late 1990s, the availability of the moderate resolution ice drift from satellite passive microwave observations (e.g., Agnew et al, 1997;Emery et al, 1997;Kwok et al, 1998) has allowed large-scale studies of drift patterns over Antarctic sea ice. The great strengths of this dataset are its spatial coverage and the length of the data record, which is more than three decades (at this writing), for the combination of SMMR, SSM/I and AMSR-E instruments.…”
Section: Introductionmentioning
confidence: 99%
“…However, these data gave only a limited picture of the ice motion field. Recently, some studies demonstrated that sequential imagery from satellite passive microwave sensors can provide observations of sea ice motion (Agnew et al 1997;Emery et al 1997;Kwok et al 1998;Liu and Cavalieri 1998;Martin and Augstein 2000;Kimura and Wakatsuchi 2000). Passive microwave measurements, which are not subject to weather conditions, provide daily views of sea ice cover, and enable routine monitoring of ice motion.…”
Section: Introductionmentioning
confidence: 99%